2018
DOI: 10.1075/ssol.19003.tur
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between fiction media, genre, and empathic abilities

Abstract: Fiction enables readers to simulate the social experiences of characters and may facilitate prosociality. Research has indicated that fiction print exposure positively relates to empathy and may promote altruistic behaviors. Whether associations hold across different media formats and thematic genres remains unclear. This study took a multidimensional approach to both fiction engagement and empathic abilities. Specifically, it aimed to replicate previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…Fiction can develop empathic accuracy through readers learning about social content, or through the process of regularly simulating the experiences of characters (Mar, 2018), and so both mentalizing and experience‐sharing processes may be enhanced through fiction (Mar & Oatley, 2008). Future research may contribute to an understanding of how far different forms of fiction, including different genres and media presentations (Black & Barnes, 2015; Fong et al, 2013; Kidd & Castano, 2013; Turner & Felisberti, 2018), support empathic accuracy using mentalizing and experience‐sharing processes.…”
Section: Discussionmentioning
confidence: 99%
“…Fiction can develop empathic accuracy through readers learning about social content, or through the process of regularly simulating the experiences of characters (Mar, 2018), and so both mentalizing and experience‐sharing processes may be enhanced through fiction (Mar & Oatley, 2008). Future research may contribute to an understanding of how far different forms of fiction, including different genres and media presentations (Black & Barnes, 2015; Fong et al, 2013; Kidd & Castano, 2013; Turner & Felisberti, 2018), support empathic accuracy using mentalizing and experience‐sharing processes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has shown positive associations between exposure to popular romance and suspense/thriller genres and performance on the RMET, not accounted for by demographic differences or exposure to nonfiction (Fong, Mullin & Mar, 2013). Self-reported enjoyment of popular genres, including comedy and romance, have found to positively correlate with the self-reported tendencies to take others' perspectives and to feel concern for others, whereas other genres (e.g., crime/thriller) were not associated with these abilities (Turner & Felisberti, 2018). Relationships between fictionexposure and social cognitive outcomes appears to vary at the level of thematic genre (see also, Black, Capps & Barnes, 2018, who examined relationships between genre-exposure and moral judgments).…”
Section: Literary and Popular Fictionmentioning
confidence: 94%
“…showing that fiction-reading led to higher explicit SST scores compared to no-reading when IRI, age, gender, comprehension of the SST text and fiction-exposure were controlled, p = .049 (p = .040 when nonfiction-exposure was controlled). Recall the proposal that literary texts contain the necessary complexities required to activate the mechanisms associated with social cognition (e.g., Hakemulder, 2000;, whereas other lines of enquiry (e.g., studies examining popular fiction; Black et al, 2018;Fong et al, 2013;Koopman, 2015;Turner & Felisberti, 2018) have indicated that such effects are not contingent on literariness. The present findings suggest that reading popular fiction may also support social cognition post-reading, and the mechanisms involved in the effects of popular narratives represent an area for further enquiry.…”
Section: Fiction-reading Versus No-readingmentioning
confidence: 99%
“…Although the issue of different affordances of media (see Magliano et al . 2013) and the modalities of their reception have been receiving deserved attention (Turner and Felisberti 2018, 265), this study's approach was unidimensional and exploratory in comparison, dealing with different facets of readers’ memory. That is to say, data was gathered only sporadically about substrates , or the physical form of the text and the paratext (see Mangen and van der Weel 2016), like the smell of the pages or the look of the front cover.…”
Section: Spontaneous Transmedia Co-locationmentioning
confidence: 99%